Is the Grandes Écoles/Universities Divide about to Disappear in France? - Musselin, Christine (International Higher Education, 2024)
This paper describes the evolution of the grandes écoles/universities divide in France. It first shows that while universities have adopted professional training programs, the grandes écoles have “universitarized.” Furthermore, in recent years, the policies aimed at the transformation of the French higher education landscape have led to some mergers including universities and grandes écoles. Nevertheless the divide between the two sectors remains consequent.